Battery super‐capacitor hybrid system for electrical vehicle transportation's systems – an energy integrated approach. Issue 3 (1st September 2020) - Rayguru, Madan Mohan; Madichetty, Sreedhar; Mishra, Sukumar
Abstract : Hybrid energy storage system (HESS) generally comprises of two different energy sources combined with power electronic converters. This article uses a battery super‐capacitor based HESS with an adaptive λ tracking control strategy. The proposed control strategy is to preserve battery life, while operating at transient conditions of the load. The proposed control strategy comprises of a gain adaptation algorithm, combined with a dead‐zone induced feedback. The closed loop system under the influence of this feedback scheme, is proved to be is robust against variation in operating conditions, parameter uncertainties and measurement noise. Unlike the earlier adaptive controllers for HESS, this strategy does not involve any parameter adaptation routine. Hence, this controller is computationally less intensive and better suited for practical applications involving uncertain environmental conditions. The efficacy of the proposed strategy is verified through numerical simulations and experimental scenarios.